Ethical Marketing Practice: A Foundational and Fundamental Virtue for Corporate Reputation/Financial Performance - Felix, Egboro; A. E., Ehikwe (British Journal of Marketing Studies, 2016)
The social and economic justification for the existence and survival of a business corporate entity is its ability to satisfy its customers through its products and services. A company meets its basic responsibility to society through its products and ethical marketing practices. A company cannot successfully sell low quality products, coupled with other sharp and corrupt practices over the long run. The dignity of the marketer must be sustained and maintained. The minimum standard, culture and value system acceptable to the public must be projected. This study is on ethical marketing practice, as a fundamental and foundational virtue for corporate reputation and financial performance. Eight pharmaceutical companies from Edo and Delta States were sampled, using a sample size of 245 staff. The multiple regression statistical technique was used to determine the extent to which standard products and services, honesty and integrity, fair prices and truthful advert predicts financial performance in a business organisation.